2018
DOI: 10.1186/s12943-017-0746-0
|View full text |Cite|
|
Sign up to set email alerts
|

microRNA-124 inhibits bone metastasis of breast cancer by repressing Interleukin-11

Abstract: BackgroundMost patients with breast cancer in advanced stages of the disease suffer from bone metastases which lead to fractures and nerve compression syndromes. microRNA dysregulation is an important event in the metastases of breast cancer to bone. microRNA-124 (miR-124) has been proved to inhibit cancer progression, whereas its effect on bone metastases of breast cancer has not been reported. Therefore, this study aimed to investigate the role and underlying mechanism of miR-124 in bone metastases of breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(127 citation statements)
references
References 46 publications
(51 reference statements)
5
122
0
Order By: Relevance
“…Also, retinoic orphan receptor-γ (RORγ) and signal transducer and activator of transcription 3 (STAT3)are the transcription factors responsible for Th17 differentiation andstabilization.Gerogios et al demonstrated that miR-124 could promote the children UC and pathogenesis by regulating the expression and phosphorylation of STAT3, but special cell type was not involved [14]. The previous study also demonstrated that miR-124 depression was related to carcinogenesis, and development by targeting different gene [23,24,25].These observations suggested that miR-124 played an key role in colitis and sporadic colon cancer.In our present study, we focused on the miR-124 function in Th17 cell and found that miR-124 could inhibit the polarization of Th17 cell and promote the transition of Th17 to treg in colitis and colitis related colon cancer by targeting stat3 gene.These results are consistent with downregulation of miR-124 developingintestinal failure with M1 macrophage phenotype by targeting stat3 and acetylcholinesterase (AChE). We believe that in the absence of miR-124 signaling cascade, the presence of intestinal commensal bacteria will drive intestinal CD4 + T helper cells toward Th17 cell polarization, resulting in a hyper-in ammatory response with associated tissue damage and pathogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…Also, retinoic orphan receptor-γ (RORγ) and signal transducer and activator of transcription 3 (STAT3)are the transcription factors responsible for Th17 differentiation andstabilization.Gerogios et al demonstrated that miR-124 could promote the children UC and pathogenesis by regulating the expression and phosphorylation of STAT3, but special cell type was not involved [14]. The previous study also demonstrated that miR-124 depression was related to carcinogenesis, and development by targeting different gene [23,24,25].These observations suggested that miR-124 played an key role in colitis and sporadic colon cancer.In our present study, we focused on the miR-124 function in Th17 cell and found that miR-124 could inhibit the polarization of Th17 cell and promote the transition of Th17 to treg in colitis and colitis related colon cancer by targeting stat3 gene.These results are consistent with downregulation of miR-124 developingintestinal failure with M1 macrophage phenotype by targeting stat3 and acetylcholinesterase (AChE). We believe that in the absence of miR-124 signaling cascade, the presence of intestinal commensal bacteria will drive intestinal CD4 + T helper cells toward Th17 cell polarization, resulting in a hyper-in ammatory response with associated tissue damage and pathogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, we speculate that SFTA1P may act as an oncogene. Our ceRNA network indicated that SFTA1P up-regulated the expressions of IL-11 or HOXC8 by binding mir-211, and elevated IL-11 or HOXC8 contributes to development of cancer , such as breast cancer (Cai et al 2018;Li et al 2014) and non-small cell lung cancer (Liu et al 2018;Zhao et al 2018b).…”
Section: Considering the Correlation Between Delncrnas And Clinical Cmentioning
confidence: 92%
“…Similarly, the reduced expression of miR-124 in metastatic bone tissue from breast cancer is associated with aggressive clinical characteristics accompanied with shorter bone metastasis-free survival and OS. Restoration of miR-124 in breast cancer cells resulted in the suppression of bone metastasis in vivo through the targeting of intrleukin-11 (IL-11) and the consequent inhibition of osteoclast progenitor cells differentiation and survival [83].…”
Section: Mirna In Bone Metastasis From Breast Cancermentioning
confidence: 99%